(untitled) (International Journal of Medical and Allied Health Sciences, 2025)
Background: Psychological stress has been recognized as a potential disruptor of the menstrual cycle in working women. However, the extent and nature of this relationship remain unclear, especially when examining specific flow patterns and menstrual symptoms. Objective: To evaluate the association between perceived stress levels and menstrual health patterns- specifically, flooding episodes and daily flow characteristics- among working women in Jaipur. Methods: A cross-sectional study was conducted on 67 working women aged 20-35 years. The Perceived Stress Scale (PSS) was used to assess stress levels, while menstrual health was evaluated using the Pictorial Blood Assessment Chart (PBAC) and a menstrual history questionnaire. Participants were categorized into low, moderate, and high stress groups based on PSS scores. Chi-square tests were applied to determine associations between stress levels and menstrual variables such as flooding episodes and flow patterns across five days. Results: No statistically significant association was found between perceived stress levels and menstrual flow on any of the five days (p-values > 0.05), with Day 3 showing the closest trend (p = 0.160). Similarly, flooding episodes were not significantly correlated with stress levels (Chi-square = 13.78, p = 0.315). The overall distribution of stress levels across different menstrual flow patterns on Day 1 also lacked significance (Chi-square = 2.50, p = 0.961). Conclusion: The findings suggest no significant correlation between perceived stress and menstrual flow characteristics or flooding episodes. While stress is an important factor in overall health, its direct impact on menstrual flow patterns in this cohort appears minimal.